2015
DOI: 10.4049/jimmunol.1401714
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Nur77 Attenuates Airway Inflammation in Mice by Suppressing NF-κB Activity in Lung Epithelial Cells

Abstract: Allergic asthma is characterized by persistent chronic airway inflammation, which leads to mucus hypersecretion and airway hyperresponsiveness. Nuclear receptor Nur77 plays a pivotal role in distinct immune and inflammatory cells and is expressed in eosinophils and lung epithelium. However, the role of Nur77 in allergic airway inflammation has not been studied so far. In the present study, we determined the role of Nur77 in airway inflammation using a murine model of OVA-induced allergic airway inflammation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…Tnfrsf8 , Anxa2 and Il1r2 are overexpressed in allergic asthmatics 3335 . Deletion of Nr4a1 , which is downregulated by IL-25 combined with NMU, exacerbates airway inflammation in mice, suggesting a potential role in limiting inflammatory ILC responses 36 .…”
Section: Il-25 Combined With Nmu Expands Inflammatory Ilc2smentioning
confidence: 99%
“…Tnfrsf8 , Anxa2 and Il1r2 are overexpressed in allergic asthmatics 3335 . Deletion of Nr4a1 , which is downregulated by IL-25 combined with NMU, exacerbates airway inflammation in mice, suggesting a potential role in limiting inflammatory ILC responses 36 .…”
Section: Il-25 Combined With Nmu Expands Inflammatory Ilc2smentioning
confidence: 99%
“…Recent interest has focused on its potent anti-inflammatory effect in inflammatory diseases and cancer. Genetic studies have revealed a critical role of Nur77 in controlling the inflammatory responses, highlighted by its protective function in atherosclerosis (Hamers et al, 2012; Hanna et al, 2012), obesity (Perez-Sieira et al, 2013), diabetes (Chao et al, 2009), asthma (Kurakula et al, 2015), arthritis (De Silva et al, 2005), and inflammatory bowel disease (Hamers et al, 2015; Wu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…An LXR agonist reduces the response to OVA-allergen challenge in a murine model of asthma [17]. NR4A attenuates airway inflammation in a mouse model of asthma [18]. These data suggest that RXRs, which act as both homodimers and heterodimers with other NRs, may be potential targets in the prevention and management of heterogeneous asthma patients.…”
Section: Introductionmentioning
confidence: 99%